Introduction: Parallel and Distributed Processing (IEEE transactions on computers, 1982)
THE GROWTH of interest in parallel and distributed processing in the last decade has been explosive. It will doubtlessly continue unabated, being the only approach to increasing the speed and power of computing systems whose ultimate limits, by fundamental physical laws or well-established theory, are not yet definable. Some of the papers that follow in this Special Issue on Parallel and Distributed Processing were originally presented at the 1981 (Tenth) International Conference on Parallel Procesing; others were submitted in response to the call for papers for the Special Issue. Being devoted to recent advances in parallel and distributed processing systems, the Special Issue covers a wide range of subjects, from architectures to algorithms, from protocols to performance evaluation. They, and other topics, may eventually justify special issues of their own.